PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN UKURAN PERUSAHAANTERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERASI - Puteri Bilqis Halimatussajidah (2021)
This study aims to determine the effect of disclosure Corporate Social Responsibility (CSR) on firm value with earnings management as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. This research is a type of quantitative research that uses secondary data, namely the company's annual report published on the Indonesia Stock Exchange (IDX). CSR disclosure is proxied using standards based on ISO 26000, company size is proxied using log total assets, earnings management is proxied using the formula Modified Jones Model, and company value is proxied using Tobin's Q. After selecting a sample using purposive sampling , a sample of 21 companies is obtained. The analysis technique used is multiple linear regression, with a significance level of 5%. The results of this study indicate that CSR disclosure has a significant negative effect on firm value, firm size has a significant positive effect on firm value, earnings management does not moderate CSR disclosure on firm value and earnings management does not moderate firm size on firm value.